Leader-member exchange (LMX) theory - Achua, Christopher F. (Henry Stewart Talks, 2022)
Vertical Dyadic Linkage, Leaders and followers’ relationship, Spotlight effect, High and low quality LMX relationships, In-group and out-group followers